Analysis of Students' Learning Skills and Innovation Skills at SMK Negeri 2 Padang Panjang - Putri, Rifka Aulia; Samudra, Ami Anggraini; Junaidi, Satrio (FKIP - Universitas Riau, 2024)
In the 21st century, there are several special skills that students must master, one of which is 21st century learning and innovation skills. This research aims to determine the level of learning and innovation skills of students at SMK Negeri 2 Padang Panjang. The variables used are 21st century skills, namely Learning and Innovation Skills, which consist of four components, namely critical thinking skills, creative thinking skills, collaboration skills and communication skills. So the sample totaled 63 people. The data collection technique uses a questionnaire. The data analysis used is descriptive analysis. The results of the research show that the skill level of students at SMK Negeri 2 Padang Panjang Abad 21 has an average percentage of 82.53% which is classified as very good. The average percentage value of each component is 80.51% for critical thinking skills, 79.56% for creative thinking skills, 89.58% for collaboration skills and 85.32% for communication skills. Based on the research results, it can be concluded that the overall level of learning and innovation skills of Vocational High School students at SMK Negeri 2 Padang Panjang is very good.